ADDITIVE ρ-FUNCTIONAL EQUATIONS IN BANACH SPACES

The Pure and Applied Mathematics.
2015.
Nov,
22(4):
375-382

- Received : October 01, 2015
- Accepted : October 12, 2015
- Published : November 30, 2015

Download

PDF

e-PUB

PubReader

PPT

Export by style

Article

Metrics

Cited by

TagCloud

In this paper, we solve the additive
ρ
-functional equations
where
ρ
is a fixed number with
ρ
≠ 1, 2, and
where
ρ
is a fixed number with
ρ
≠ 1.
Using the direct method, we prove the Hyers-Ulam stability of the additive
ρ
-functional equations (0.1) and (0.2) in Banach spaces.
is called the
Cauchy equation
. In particular, every solution of the Cauchy equation is said to be an
additive mapping
. Hyers
[3]
gave a first affirmative partial answer to the question of Ulam for Banach spaces. Hyers’ Theorem was generalized by Aoki
[1]
for additive mappings and by Rassias
[4]
for linear mappings by considering an unbounded Cauchy difference. A generalization of the Rassias theorem was obtained by Gǎvruta
[2]
by replacing the unbounded Cauchy difference by a general control function in the spirit of Rassias’ approach.
In Section 2, we solve the additive functional equation (0.1) and prove the Hyers-Ulam stability of the additive functional equation (0.1) in Banach spaces.
In Section 3, we solve the additive functional equation (0.2) and prove the Hyers-Ulam stability of the additive functional equation (0.2) in Banach spaces.
Throughout this paper, assume that
X
is a normed space and that
Y
is a Banach space.
ρ
be a number with
ρ
≠ 1, 2.
We solve and investigate the additive
ρ
-functional equation (0.1) in normed spaces.
Lemma 2.1.
If a mapping f
:
X
→
Y satisfies
for all x
,
y
,
z
∈
X
,
then f
:
X
→
Y is additive
.
Proof
. Assume that
f
:
X
→
Y
satisfies (2.1).
Letting
x
=
y
=
z
= 0 in (2.1), we get −2
f
(0) = −
ρf
(0). So
f
(0) = 0.
Letting
y
=
x
and
z
= 0 in (2.1), we get
f
(2
x
)−2
f
(
x
) = 0 and so
f
(2
x
) = 2
f
(
x
) for all
x
∈
X
. Thus
for all
x
∈
X
.
It follows from (2.1) and (2.2) that
and so
f
(
x
+
y
+
z
) =
f
(
x
) +
f
(
y
) +
f
(
z
) for all
x, y, z
∈
X
. Since
f
(0) = 0,
for all
x
,
y
∈
X
. ☐
We prove the Hyers-Ulam stability of the additive
ρ
-functional equation (2.1) in Banach spaces.
Theorem 2.2.
Let φ
:
X
^{3}
→ [0, ∞)
be a function and let f
:
X
→
Y
be a mapping satisfying
f
(0) = 0
and
for all x
,
y
,
z
∈
X
.
Then there exists a unique additive mapping A
:
X
→
Y such that
for all x
∈
X
.
Proof
. Letting
y
=
x
and
z
= 0 in (2.4), we get
for all
x
∈
X
. So
for all
x
∈
X
. Hence
for all nonnegative integers
m
and
l
with
m
>
l
and all
x
∈
X
. It follows from (2.7) that the sequence
is Cauchy for all
x
∈
X
. Since
Y
is a Banach space, the sequence
converges. So one can define the mapping
A
:
X
→
Y
by
for all
x
∈
X
. Moreover, letting
l
= 0 and passing the limit
m
→ ∞ in (2.7), we get (2.5).
Now, let
T
:
X
→
Y
be another additive mapping satisfying (2.5). Then we have
which tends to zero as
q
→ ∞ for all
x
∈
X
. So we can conclude that
A
(
x
) =
T
(
x
) for all
x
∈
X
. This proves the uniqueness of
A
.
It follows from (2.3) and (2.4) that
for all
x
,
y
,
z
∈
X
. So
for all
x
,
y
,
z
∈
X
. By Lemma 2.1, the mapping
A
:
X
→
Y
is additive. ☐
Corollary 2.3.
Let
r
> 1
and θ be nonnegative real numbers, and let f
:
X
→
Y
be a mapping satisfying f
(0) = 0
and
for all x
,
y
,
z
∈
X
.
Then there exists a unique additive mapping A
:
X
→
Y such that
for all x
∈
X
.
Proof
. Letting
φ
(
x
,
y
,
z
) :=
in Theorem 2.2, we get the desired result. ☐
Theorem 2.4.
Let φ
:
X
^{3}
→ [0, ∞)
be a function and let f
:
X
→
Y be a mapping satisfying f
(0) = 0, (2.4)
and
for all x
,
y
,
z
∈
X
.
Then there exists a unique additive mapping A
:
X
→
Y such that
for all x
∈
X
.
Proof
. It follows from (2.6) that
for all
x
∈
X
. Hence
for all nonnegative integers
m
and
l
with
m
>
l
and all
x
∈
X
. It follows from (2.10) that the sequence
is a Cauchy sequence for all
x
∈
X
. Since
Y
is complete, the sequence
converges. So one can define the mapping
A
:
X
→
Y
by
for all
x
∈
X
. Moreover, letting
l
= 0 and passing the limit
m
→ ∞ in (2.10), we get (2.9).
The rest of the proof is similar to the proof of Theorem 2.2. ☐
Corollary 2.5.
Let r
< 1
and θ be nonnegative real numbers, and let f
:
X
→
Y
be a mapping satisfying f
(0) = 0
and
(2.8).
Then there exists a unique additive mapping A
:
X
→
Y such that
for all x
∈
X
.
Proof
. Letting
φ
(
x
,
y
,
z
) :=
in Theorem 2.4, we get the desired result. ☐
ρ
be a number with
ρ
≠ 1.
We solve and investigate the additive
ρ
-functional equation (0.2) in normed spaces.
Lemma 3.1.
If a mapping f
:
X
→
Y satisfies
for all x
,
y
,
z
∈
X
,
then f
:
X
→
Y is additive
.
Proof
. Assume that
f
:
X
→
Y
satisfies (3.1).
Letting
x
=
y
=
z
= 0 in (2.1), we get -2
f
(0) = -2
ρf
(0). So
f
(0) = 0.
Letting
y
=
x
and
z
= 0 in (2.1), we get
f
(2
x
)-2
f
(
x
) = 0 and so
f
(2
x
) = 2
f
(
x
) for all
x
∈
X
. Thus
for all
x
∈
X
.
It follows from (3.1) and (3.2) that
and so
for all
x
,
y
∈
X
. ☐
We prove the Hyers-Ulam stability of the additive
ρ
-functional equation (3.1) in Banach spaces.
Theorem 3.2.
Let φ
:
X
^{3}
→ [0, ∞)
be a function and let f
:
X
→
Y be a mapping satisfying f
(0) = 0
and
for all x
,
y
,
z
∈
X
.
Then there exists a unique additive mapping A
:
X
→
Y such that
for all x
∈
X
.
Proof
. Letting
y
=
x
and
z
= 0 in (3.3), we get
for all
x
∈
X
.
The rest of the proof is similar to the proof of Theorem 2.2. ☐
Corollary 3.3.
Let r
> 1
and θ be nonnegative real numbers, and let f
:
X
→
Y be a mapping satisfying f
(0) = 0
and
for all x
,
y
,
z
∈
X
.
Then there exists a unique additive mapping A
:
X
→
Y such that
for all x
∈
X
.
Proof
. Letting
φ
(
x
,
y
,
z
) :=
in Theorem 3.2, we get the desired result. ☐
Theorem 3.4.
Let φ
:
X
^{3}
→ [0, ∞)
be a function and let f
:
X
→
Y be a mapping satisfying f
(0) = 0, (3.3)
and
for all x
,
y
,
z
∈
X
.
Then there exists a unique additive mapping A
:
X
→
Y such that
for all x
∈
X
.
Proof
. It follows from (3.4) that
for all
x
∈
X
.
The rest of the proof is similar to the proofs of Theorems 2.2 and 2.4. ☐
Corollary 3.5.
Let r
< 1
and θ be nonnegative real numbers, and let f
:
X
→
Y be a mapping satisfying f
(0) = 0
and
(3.5).
Then there exists a unique additive mapping A
:
X
→
Y such that
for all x
∈
X
.
Proof
. Letting
φ
(
x
,
y
,
z
) :=
in Theorem 3.4, we get the desired result. ☐

1. INTRODUCTION

The stability problem of functional equations originated from a question of Ulam
[5]
concerning the stability of group homomorphisms.
The functional equation
PPT Slide

Lager Image

2. ADDITIVEρ-FUNCTIONAL EQUATION (0.1)

Let
PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

3. ADDITIVEρ-FUNCTIONAL EQUATION (0.2)

Let
PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

PPT Slide

Lager Image

Aoki T.
(1950)
On the stability of the linear transformation in Banach spaces
J. Math. Soc. Japan
2
64 -
66
** DOI : 10.2969/jmsj/00210064**

Gǎvruta P.
(1994)
A generalization of the Hyers-Ulam-Rassias stability of approximately additive mappings
J. Math. Anal. Appl.
184
431 -
443
** DOI : 10.1006/jmaa.1994.1211**

Hyers D.H.
(1941)
On the stability of the linear functional equation
Proc. Natl. Acad. Sci. U.S.A.
27
222 -
224
** DOI : 10.1073/pnas.27.4.222**

Rassias Th.M.
(1978)
On the stability of the linear mapping in Banach spaces
Proc. Amer. Math. Soc.
72
297 -
300
** DOI : 10.1090/S0002-9939-1978-0507327-1**

Ulam S.M.
1960
A Collection of the Mathematical Problems
Interscience Publ.
New York

Citing 'ADDITIVE ρ-FUNCTIONAL EQUATIONS IN BANACH SPACES
'

@article{ SHGHCX_2015_v22n4_375}
,title={ADDITIVE ρ-FUNCTIONAL EQUATIONS IN BANACH SPACES}
,volume={4}
, url={http://dx.doi.org/10.7468/jksmeb.2015.22.4.375}, DOI={10.7468/jksmeb.2015.22.4.375}
, number= {4}
, journal={The Pure and Applied Mathematics}
, publisher={Korean Society of Mathematical Education}
, author={JUN, IN WHAN
and
SEO, JEONG PIL
and
LEE, SUNGJIN}
, year={2015}
, month={Nov}